The treatment of Multimodality in Childhood and Primary Education. The Spanish case under the LOMLOE curriculum - López Pena, Zósimo (Didáctica. Lengua y Literatura, 2024)
Multimodality is a discipline or methodological approach that draws on social semiotics and is concerned with the meaning that is created through different configurations and combinations of communication modes. The new curricula for Infant and Primary Education in the Spanish education system, which came into force in September 2022, following the publication of Organic Law 3/2020 of 29 December, have introduced some new features in educational stages. One of these, which explicitly affects non-university education, is the inclusion of multimodality. The aim of this article is to analyse the treatment given to multimodality in the curricula of the educational stages of Infant and Primary Education in Spain. The aim of this paper is to understand the subjects in which multimodality has been given a place and the interpretation or uses made of the discipline in the national and regional curricula, with particular attention to those subjects linked to languages, literature and their didactics.